Primary spinal primitive neuroectodermal tumor on MR imaging - Thoriya, Prashant J; Watal, Pankaj; Bahri, Nandini U; Rathod, Ketan (Indian Journal of Radiology and Imaging, 2015)
Neoplasms in the region of filum terminale are not uncommon. Myxopapillary ependymoma is the commonest tumor at this location. The differentials reported for this entity are nerve sheath tumor, meningioma, paraganglioma, intradural metastases, lymphoma, other varieties of ependymoma, subependymoma, astrocytoma, ganglioglioma, hemangioblastoma, and primitive neuroectodermal tumor (PNET). PNET may very rarely present as an intradural thoracolumbar mass. We present pre- and post-therapy magnetic resonance imaging (MRI) features of a patient with proven primary spinal primitive neuroectodermal tumor (PSPNET) of peripheral subtype.
Keywords: CD99; myxopapillary ependymoma; primary spinal primitive neuroectodermal tumor; primitive neuroectodermal tumor; spinal